Research Gap in Sustainopreneurship - Amir, Aghelie; Sorooshian, Shahryar; Noor Azlinna, Azizan (Informatics Publishing Limited, 2016)
Entrepreneurs or the move towards self‐employment is, and will continue to become, an increasingly important element of economic growth and development. It is now recognized that small firms in a nation are "net creators of jobs in a society with major impact on living lifestyle. Entrepreneurs are essential tools for growth and improving wealth of a society by contributing jobs to people to raise money supply for the economy to develop a nation. In order for entrepreneurs to have positive long term effect, they need to have sustainable successful business in order to be prosper in their competition in their industries and promise success for the country. In facing the challenges of reducing harmful environmental and societal impacts created by current Unsustainable business practices, sustainable entrepreneurship (or sustainopreneurship) is increasing in importance because it can lead to a socially, economically, and environmentally sustainable society. Firms can solve social and environmental problems and be economically self-sustaining at the same time. Innovation is seen as key to find new solutions for environmental sustainability. Furthermore, scholars see stakeholder engagement as a new solution to create innovations for sustainability and environmental sustainability in particular. Since there have only been few empirical studies in sustainable entrepreneurship ,the conditions, processes, features and outcomes that distinct this form of entrepreneurship are yet to be defined. Sustainability entrepreneurship is new breed in entrepreneurship world and they are very limited researchers have taken regarding such issue. More researchers need to be done to provide conceptual basis for stimulating scholarly thought and improving the understanding of sustainable entrepreneurship as an important field within entrepreneurship research and to perceive ultimate and definite concept of sustainability entrepreneurship.